Effectiveness, tolerability, and dropout rates of vortioxetine in comorbid depression: A naturalistic study. (14th July 2020) - De Carlo, Vera; Vismara, Matteo; Grancini, Benedetta; Benatti, Beatrice; Bosi, Monica Francesca; Colombo, Anna; Viganò, Caterina Adele; Dell'Osso, Bernardo
Abstract: Objective: Vortioxetine is a novel antidepressant whose safety, tolerability, and therapeutic action have been supported by several studies. The present naturalistic study aimed to characterize its effectiveness, tolerability, and dropout rate in the real world. Methods: Total sample consisted of 66 outpatients with major depressive episode, treated with vortioxetine, whose clinical variables were evaluated over three time points. Results: Most common primary diagnoses were major depressive disorder (45.5%) and bipolar disorder (33.4%), with an overall comorbidity rate of 48.5% and concomitant medications in the 89.4%. The mean vortioxetine daily dosage was 12.90 ± 5.65 mg. Effectiveness of vortioxetine through a significant improvement on specific psychometric scales emerged, while only a nonsignificant trend of association between higher dosage and effectiveness was found. In the total sample, 51.5% were classified as responders and 36.4% as remitters. Two‐thirds of subjects did not report side effects, while in the remaining patients, gastrointestinal ones were the most frequent (72.7%). Almost two‐thirds of the sample could complete the follow‐up, while 36.4% dropped out; the main reasons for dropout were side effects (37.5%) and lack of efficacy (29.2%). Conclusions: Larger sample studies are warranted to better characterize vortioxetine effectiveness and tolerability in the real world.